RANCANG BANGUN ROBOT PEMADAM API BERODA DENGAN NAVIGASI SENSOR KOMPAS BERBASIS ATMEGA 128 - Nurul hilal, Yusuf; Heranurweni, Sri; Kurniawan N, Andi (Universitas Semarang, 2017)
CMPS03 an electronic compass sensor navigation sensor that helps in determining the direction toward the robot and in tracing the wall or room that works according to the principle of the compass in general. CMPS03 electronic compass sensor has two sensors that will detect ferrous magnetic Earth's magnetic field and also has a range of angles 360Ëš, the resulting data is then sent to the microcontroller Keywords: Compass Sensor, Robot, and Microcontroller.